Balancing benefits and challenges: Tourism’s associations with residents’ quality of life, solidarity, and support across development stages - Xiaoqing Jiang (PLoS ONE, 2026)
As host–tourist tensions increase in popular destinations, it is essential to understand how tourism relates to residents’ quality of life, attitudes, and supportive behaviors. This study explores these impacts in Qingdao, a city with mature tourism development, and Zhoushan, a city undergoing rapid tourism growth. Survey data were collected from 508 residents in Qingdao and 362 in Zhoushan through an online questionnaire using stratified random sampling to ensure representativeness. After data cleaning and validation, structural equation modeling was used to test the proposed hypotheses. Additional analyses included descriptive statistics, t-tests, confirmatory factor analysis, and multi-group analysis to examine moderating effects. The results indicate that tourism is associated with residents’ quality of life and emotional solidarity, which are in turn linked to their attitudes and supportive behaviors. Emotional closeness and empathy show strong links with support, while not all quality-of-life aspects correspond to similar emotional responses. In Qingdao, tourism employment negatively moderates the attitude–support link, whereas no significant effect is found in Zhoushan. These findings refine Social Exchange Theory by highlighting emotional and contextual conditions under which resident support varies. Practically, the study outlines stage-specific implications for balancing tourism growth with resident well-being through targeted emotional engagement and employment quality improvement.